GUIDANCE STRATEGIES FOR VULNERABLE FAMILIES IN THE INCLUSION OF 3 TO 5-YEAR-OLD CHILDREN IN PRESCHOOL EDUCATION IN THE ZANGO DISTRICT - José Correia Lucena, Madalena; Manuel Correia Filho, João (Revista Gênero e Interdisciplinaridade, 2025)
Family guidance in educational contexts is a set of training and intervention actions with the family on specific topics and realities, in the best interest of the children and the proper functioning of the family system as the foundational unit of social life. Thus, the purpose of this article is to propose a system of activities to guide vulnerable families of children aged three to five years old in Preschool Education in one of the neighborhoods of the Zango District, through participatory techniques that enable their integration into the educational context. In this regard, the study relied on a qualitative methodology, configured as a case study based on bibliographic and documentary review, which supported the observation and interview. Consequently, it was found that the study enabled family involvement in the education of their children; behavior modeling and control; motivation; and activities integrated into family routines. Therefore, it was possible to positively impact the families’ awareness of the importance of preschool education for their children.